دراسة انتشار أشكال سوء الإطباق في المستويات الثلاثة عند أطفال الساحل السوري في فترة الإطباق المختلط - حسن, حازم; تيزيني, محمد; ابراهيم, أشرف (Latakia University Journal -Medical Sciences Series, 2013)
يعد سوء الإطباق من أكثر المشاكل السنية شيوعا. تهدف هذه الدراسة الى التحري عن انتشار حالات سوء الإطباق في مجتمع الساحل السوري. أجريت الدراسة على عينة مكونة من 1200 مريض في فترة الإطباق المختلط (569 ذكر– 631 أنثى) وكان متوسط العمر الزمني للمرضى (8.65±1.4 سنة للذكور-8.64±1.36 سنة للإناث). أظهرت الدراسة انتشار سوء الإطباق بنسبة 84.8% عند أفراد العينة. و بلغت هذه النسبة انتشار سوء الإطباق 84% بالمستوى السهمي و58.33% بالمستوى العمودي و37.8% بالمستوى المعترض. وأوصت الدراسة بالعمل على زيادة الوعي الصحي لدى المجتمع بما يساهم في الوقاية من هذه المشاكل وعلاجها بأفضل السبل ان وجدت. Malocclusion is considered one of the most prevalent dental problems .This research aimed to study the prevalence of malocclusion states in the Syrian coast community. The sample of study consists of 1200 patients in mixed dentition stage (569 males – 631 females) with mean age (8.65 ± 1.4 years for male, 8.64 ±1.36 years for females). The study showed a prevalence of malocclusion in about 84.8% of the sample, with about 58.33% for vertical plane malocclusion and 84% for sagittal plane malocclusion, and 37.8% for transversal plane malocclusion. We concluded that it is very important to improve the hygiene awareness between our community population for better prevention and treatment of these problems.